Randomized controlled trial on effect of different routes of dexmedetomidine on Haemodynamics in patients undergoing saphenectomy under epidural anaesthesia - Sisi Zeng; Jixiang Wan; Xuechao Li; Na Wang; Jiabei Li; Luyue Gao; Zhen Yang; Fangjun Wang (Scientific Reports)
Abstract The effect of epidural infusion of dexmedetomidine on haemodynamics is unclear. This study aimed to explore the effects of epidural or intravenous infusion of dexmedetomidine on haemodynamics during lower extremity varicose veins surgery (saphenectomy) under epidural anaesthesia. Ninety patients were randomly allocated to three groups: ED group (epidural: 0.59% ropivacaine plus 0.5 µg/kg dexmedetomidine, intravenous: normal saline), VD group (epidural: 0.59% ropivacaine plus normal saline, intravenous: 0.5 µg/kg dexmedetomidine), or NS group (epidural: 0.59% ropivacaine plus normal saline, intravenous: normal saline). The primary outcome was the systolic blood pressure (SBP) at before anaesthesia (T0) and at 5 (T1), 15 (T2), and 30 min (T3) and 1 (T4), 2 (T5), 4 (T6), 6 (T7), and 8 h (T8) after dexmedetomidine infusion. The secondary outcomes were diastolic blood pressure (DBP) and heart rate (HR) at T0 − 8, plasma norepinephrine (NE), myocardial oxygen consumption (MVO2) and anesthesia efficacy. Adverse reactions and other general data were also recorded. Compared with those in the NS group, the SBP at T3 − 7 and DBP at T4 − 5,7 were significantly lower in the ED group (P = 0.008, 0.001, 0.001, 0.001, 0.038 and P = 0.017, 0.006, 0.044, respectively), and the SBP and DBP at T1 − 8 were lower in the VD group (P < 0.001, 0.001, 0.001, 0.001, 0.004 and P < 0.001, 0.001, 0.001, 0.002, 0.001, 0.001, 0.001, 0.036, respectively). The SBP and DBP at T1 − 2 in the ED group were greater than those in the VD group (P = 0.021, 0.01 and P = 0.001, 0.011, respectively). The HR at T3 − 4,6−7 was lower in the ED group than in the NS group (P < 0.001, 0.021, 0.002, 0.004, respectively). Compared with that in the VD group, the HR in the ED group at T7 was significantly lower (P < 0.001). Anaesthesia efficiency was improved in the ED group compared with VD and NS groups. The incidence of hypotension was lower in the ED group than in the VD group (P = 0.003). The combination of 0.5 µg/kg dexmedetomidine and 0.59% ropivacaine for epidural anaesthesia provides more stable haemodynamics with a lower incidence of hypotension and improved efficiency of epidural anaesthesia in patients undergoing saphenectomy.